Application of Six Sigma metrics for assessing the quality management of biochemical analytes in the clinical laboratory - Saurabh Singh; Manisha Singh; Devesh Sharma; Ijen Bhattacharya; Mamta Padhy; Surabhi Puri; Utkarsh Singh Tomar (Asian Journal of Medical Sciences, 2024)
Background: Quality control (QC) is an important part of clinical laboratory management which evaluates and maintains the performance of the clinical laboratory. Six Sigma is a continuous quality improvement process which is widely applied in the health care industry mainly in clinical laboratories. Aims and Objectives: The study aimed to evaluate the performance of biochemical analytes in a clinical laboratory using Six Sigma metrics and to implement quality improvement interventions. Sigma value was analyzed using bias, coefficient of variation (CV), and total allowable error (TEa) for each analyte. The quality goal index ratio was calculated to identify specific types of errors to introduce targeted quality interventions. Materials and Methods: This quasi-experimental study was carried out at the Government Institute of Medical Sciences, Greater Noida, Uttar Pradesh. Internal QC (IQC) and external QC data were collected during the study period and analyzed. The CV, Bias, and TEa were used to calculate the sigma (σ) values for 20 biochemical analytes. Results: On retrospective data analysis, triglycerides-Level 1 (L1) and Level 2 (L2), and direct bilirubin-L2 showed a world-class performance (above 6σ) while 14 parameters were placed below average (<3σ) on sigma metrics. Prospective data analysis was performed following quality improvement intervention. Amylase, direct bilirubin, triglycerides and alanine transferase performed at world-class sigma metric for both the control levels (L1 and L2) whereas, Albumin and aspartate transferase showed above six sigma values for L2 control only. Five analytes out of 20 performed below average (<3σ) on sigma metrics, for which further continuous intervention will be carried out. Conclusion: Six Sigma metrics is a continuous improvement and monitoring program that should be implemented to achieve world-class quality performance.